PENINGKATAN PEMAHAMAN PENJUMLAHAN DENGAN TEKNIK MENYIMPAN MENGGUNAKAN ALAT PERAGA DI KELAS II SD NEGERI 218/LIMBUR BARU - Santi, Yeni; Abdulah (Jurnal Muara Olahraga, 2024)
ABSTRACT The research problem is the lack of understanding of the material for calculating sequential additions. The aim of this research is to improve understanding of compound addition material by storing techniques through the use of number value racks. Class II students at SD Negeri 218 Limbur who have mild intellectual disabilities will benefit from a better understanding of the concept of multilevel addition operations. This type of research is called Classroom Action Research (PTK). This research was carried out in two cycles, each cycle being carried out in three meetings. Each cycle has four interrelated phases: observation, reflection, action implementation, planning phase, and reflection. The research subjects were four students of SD Negeri 218 Limbur class II. Data was collected through test and observation methods. Quantitative analysis was carried out on the data, and a table was presented showing student learning outcomes. Based on the results of research conducted in cycle I and cycle II, the results of data analysis and reflection show that cycle I research has not met the expected indicators of success, namely better understanding of mathematical concepts because it shows learning outcomes and students' abilities in understanding and carrying out sequential addition operations. using the saving technique, then the average result in cycle II was 62.5%. By using the saving technique, students were able to understand the concept of sequential addition, which not only achieved the desired goal but also improved. This shows that the use of the number value rack display tool can improve students' understanding of the addition material using storing techniques. Keywords : stacked addition, rack of number values.